GREBP, a cGMP-response Element-binding Protein Repressing the Transcription of Natriuretic Peptide Receptor 1 (NPR1/GCA) - Martel, Guy (American Society for Biochemistry and Molecular Biology, 2010)
NPR1/GCA (natriuretic peptide receptor 1/guanylyl cyclase A) expression is controlled by several agents, including ANP (atrial natriuretic peptide). After ANP stimulation, NPR1/GCA down-regulates the transcriptional activity of its gene via a cGMP-dependent mechanism. Because we previously identified a cis-acting element responsible for this cGMP sensitivity, we proceed here to explore novel putative protein binding to cGMP-response element (cGMP-RE). Using the yeast one-hybrid technique with a human kidney cDNA library, we identified a strong positive clone able to bind cGMP-RE. The clone was derived from 1083-bp-long cDNA of a gene of yet unknown function localized on human chromosome 1 (1p33.36). We named this new protein GREBP (for cGMP-response element-binding protein). DNA binding assays showed 18-fold higher cGMP-RE binding capacity than the controls, whereas an electromobility shift assay indicated a specific binding for the cGMP-RE, and chromatin immunoprecipitation confirmed the binding of GREBP to the element under physiological conditions. By acting on cGMP-RE, GREBP inhibited the expression of a luciferase-coupled NPR1 promoter construct. In H295R cells, ANP heightened GREBP expression by 60% after just 3 h of treatment while inhibiting NPR1/GCA expression by 30%. Silencing GREBP with specific small interfering RNA increased the activity of the luciferase-coupled NPR1 promoter and GCA/NPR1 mRNA levels. GREBP is a nuclear protein mainly expressed in the heart. We report here the existence of a human-specific gene that acts as a transcriptional repressor of the NPR1/GCA gene.